2010
DOI: 10.2320/matertrans.m2009337
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Friction Stir Spot Welded Galvanized Steel

Abstract: Joints of galvanized steel were obtained by friction stir spot welding (FSSW) with lap configuration using CPS design tool. No mechanically mixed layer was formed between the top and bottom plates at the weld nugget due to the limited tool penetration and the lower pin height of the welding tool than the steel plate thickness. A deformed region, in which ZnO particles were detected, was observed in the joint. The formation of this deformed region was attributed to the explosion of the Zn coating layer due to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Li et al [25] reported that plunge depth increased with the increase of dwell time and plunge rate on the pinless friction stir spot welding of AA2024. Similarly, Baek et al [23] showed that gap at the joint edge region decreased with increasing of tool plunge depth.…”
Section: Macrostructure and Microstructure Of Fssw Jointsmentioning
confidence: 83%
See 1 more Smart Citation
“…Li et al [25] reported that plunge depth increased with the increase of dwell time and plunge rate on the pinless friction stir spot welding of AA2024. Similarly, Baek et al [23] showed that gap at the joint edge region decreased with increasing of tool plunge depth.…”
Section: Macrostructure and Microstructure Of Fssw Jointsmentioning
confidence: 83%
“…For joints of galvanized steel, white layer was found at the top sheets in all samples. Authors explained it to the phase transformation of galvanized steel or the reaction between the tool and steel sheets [23].…”
Section: Macrostructure and Microstructure Of Fssw Jointsmentioning
confidence: 99%
“…The melting and boiling temperatures of Zn are 693 K (420°C) and 1180 K (907°C), respectively, welding peaks temperatures especially at the tool/workpiece contact region are expected to be higher than the boiling temperature of Zn, and thus, the possibility of Zn present in the stirred zone (SZ) should be low. Beak et al [17] explained the existence of Zn in the stirred zone as a result of a tool effect, whereby Zn will melt and evaporate during FSW, but because there is no way for it to escape outside the tool/workpiece contact region, it will explode into the SZ. In this paper, an interpretation to coalesce Zn with other elemental segregation in W2 FSW sample can be as follows: (a) The centrifugal forces from FSW tool are pushing the steel including the Zn-coated layer at tool/workpiece contact surface to the advancing-trailing side during the FSW.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature was 430ºC at the interface and 310º C near the center and edge nugget. Based on these data, Zn layer melted or softened under the FSSW tool rotation [29], [30]. The distribution of Zn will better if it is illustrated in quantitative measurement.…”
Section: Fig 2 Geometry and Zones Of Fssw Jointmentioning
confidence: 99%